Garden Fleahopper, Halticus bractatus (Say) - John L. Capinera (EDIS)
This document is EENY-078, one of a series of Featured Creatures from the Entomology and Nematology Department, Florida Cooperative Extension Service, Institute of Food and Agricultural Sciences, University of Florida. Published: March 1999. Revised: October 2001.